2017
DOI: 10.1097/qad.0000000000001643
|View full text |Cite
|
Sign up to set email alerts
|

Serum glycan-binding IgG antibodies in HIV-1 infection and during the development of broadly neutralizing responses

Abstract: Background The HIV-1 envelope is covered with glycans that provide structural integrity and protect conserved regions from host antibody responses. However, these glycans are often the target of broadly neutralizing antibodies (bNAbs) that emerge in some HIV infected individuals. We aimed to determine whether anti-glycan IgG antibodies are a general response to HIV-1 infection or specific to individuals who develop bNAbs. Methods IgG binding to glycans was assessed using arrays that contained 245 unique comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…We previously profiled anti-glycan IgG and IgM antibodies present in serum samples from 20 healthy individuals obtained yearly over a 3-year time frame. 15 To facilitate a better understanding of our new results, we carried out additional analyses on that data. Over this longer timer interval, anti-glycan antibody profiles were very consistent but had a slightly higher level of variability than over weeks to months.…”
Section: Resultsmentioning
confidence: 99%
“…We previously profiled anti-glycan IgG and IgM antibodies present in serum samples from 20 healthy individuals obtained yearly over a 3-year time frame. 15 To facilitate a better understanding of our new results, we carried out additional analyses on that data. Over this longer timer interval, anti-glycan antibody profiles were very consistent but had a slightly higher level of variability than over weeks to months.…”
Section: Resultsmentioning
confidence: 99%
“…Pooled IgG from healthy donors and IVIG (von Gunten et al, 2009;Schneider et al, 2015) have been profiled on a variety of different microarray platforms and have revealed a large diversity of antiglycan antibody repertoires, including antibodies specific for cellulose and monosaccharides (Schwarz et al, 2003). Individual serum has been tested from healthy individuals (Muthana and Gildersleeve, 2016) as well as in HIV positive individuals (Scheepers et al, 2017) from the array platforms generated by Gildersleeve's group (see discussion in section Other Approaches in Glycan Microarray Generation). We have also surveyed the anti-carbohydrate antibody repertoire (ACAR) of 105 healthy donors, ranging from 20 to 60+ years old on the NCFGv1 array (Luetscher et al in review).…”
Section: Characterization Of Natural Human Anti-glycomementioning
confidence: 99%
“…67 In these cases, antibodies to self-glycans were present in fewer patients and for fewer glycans than what we observed in COVID-19 patients. In prior studies, we found that serum IgG and IgM levels to nearly all glycans on our array are stable over time frames of up to 3 years, 66,68 indicating that high signals in certain patients are not simply due to high variability or random fluctuations over time. Lastly, our prior studies on healthy subjects of varying age indicate that these high antibody populations are not merely due to increasing age.…”
Section: Discussionmentioning
confidence: 62%
“…For example, we did not observed high antibodies to these glycans in ~100 cancer patients prior to or after vaccination with a live-attenuated poxvirus-based vaccine (PROSTVAC-VF), 64,65 indicating that they are not due to a general effect of disease or a non-specific effect of viral infection. Some instances where we have observed high antibodies to some of the glycans are HIV infected patients (antibodies to Man9, GT2, and GT3) 66 and cancer patients immunized with a whole cell cancer vaccine (antibodies to GM2, GM3, Gb5, and sialyl Lewis X). 67 In these cases, antibodies to self-glycans were present in fewer patients and for fewer glycans than what we observed in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation